Comparative Evaluation of Microbiota Dynamics and Metabolites Correlation Between Spontaneous and Inoculated Fermentations of Nanfeng Tangerine Wine - Qiu, Xiangyu; Yu, Linlin; Wang, Weiying; Yan, Riming; Zhang, Zhibin; Yang, Huilin; Zhu, Du; Zhu, Bo (Frontiers in Microbiology, 2021)
Understanding the evolution of microorganisms and metabolites during wine fermentation is essential for controlling its production. The objective of this study was to explore the core functional microbiota for the production of volatile flavors during spontaneous fermentation (SF) and inoculated fermentation (IF) of Nanfeng tangerine wine. Microbiological analysis based on high-throughput sequencing (HTS) technology revealed that Lactobacillus and Acetobacter were the dominant bacteria in SF and IF, respectively. Furthermore, the main fungal genera in SF were Hanseniaspora, Pichia, and Saccharomyces with a clear succession, whereas those in IF were Hanseniaspora, Saccharomyces, and Pichia. The qualitative and quantitative properties of the major flavor metabolites were analyzed via ultraperformance liquid chromatography and headspace–gas chromatography–mass spectrometry. SF wine was characterized by abundant esters and higher amounts of volatile acids, whereas IF wine contained higher amounts of alcohols. Analysis of the potential correlations between microbiota succession and volatile flavor dynamics revealed that Lactobacillus, Acetobacter, Hanseniaspora, and Saccharomyces were the major contributors to the production of the volatile flavor of Nanfeng tangerine wine. The results of the present study can be used to develop effective strategies for selecting beneficial bacterial and fungal strains to improve the quality of Nanfeng tangerine wine.